Yield of green beans subjected to continuous and pulse drip irrigation with saline water - Willian F. de Almeida; Vital P. da S. Paz; Ana P. C. de Jesus; Jucicléia S. da Silva; Karoline S. Gonçalves; Andressa S. de Oliveira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT In view of the imminent need for efficient water use and the search for adequate management techniques to reduce the effect of salinity on plants, a study was conducted to evaluate the effect of continuous and pulses drip irrigation with saline water on green bean yield and water use efficiency. The experiment was conducted in a greenhouse, in a completely randomized design, with treatments distributed in a 2 x 5 factorial arrangement. The first factor was type of drip irrigation, i.e., continuous or pulse, while the second factor was the levels of water salinity (electrical conductivity of 0.3, 1.5, 2.5, 3.5 and 4.5 dS m-1), with five replicates, and two plants per replicate, totaling 50 experimental units. The following variables were analysed: production of pods per pot, water use efficiency and the electrical conductivity of the soil saturation extract. According to the results, significant effect of the interaction and decreasing linear fits in response to salinity occurred for all variables studied. It was possible to note that pulse drip irrigation reduced the negative effects of irrigation water salinity on green bean yield and increased water use efficiency.